Pathways to a Succesful Career: Unveiling the PostGraduate Journey – A Tracer Study - Parcasio, Imelda G; Dolendo, Russell B; Langaoen, Brenda A; Lubrica, Percyveranda A (Social Sciences, Humanities and Education Journal (SHE Journal), 2024)
This Tracer Study looked into the contributions of the Program Doctor of Philosophy major in Educational Management to the employment status, professional growth , contribution of curricular activities to its graduates as well as the benefits they received from finishing the program. Recommendations for the improvement of the offerings were also sought. The descriptive survey was utilized to gather data from the respondents (n=66). Triangulation was used to validate the data. Results show that a high percentage of the respondents are employed in the government, with permanent status and got promoted after finishing the degree. The greatest contributions of the degrees to the professional competencies of the respondents include: the performance of independent work, critical thinking and intellectual and moral discourses; and evaluation of services and programs offered to clients. The curricular activities namely: research-based activities, core course offerings and major field offerings were the greatest contributors to the professional growth of the graduates. The benefits that the respondents enjoy are job promotions and salary increase, prestige and awards. The recommendations for the improvement of program are: more partnerships and strengthened community extension activities, improved admission policies, curricular and additional PhD Program offerings, strengthening of research and publication endeavors.